Aging agricultural labor force, outsourcing service of pest control and biopesticide application: a case study of 10 counties in Fujian Province - Shen, Doudou; Wang, Linping; Cai, Liangmei (Frontiers in Sustainable Food Systems, 2024)
Under the background of increasingly severe aging of agricultural labor force and relatively slow land circulation, agricultural production outsourcing has become the main means of agricultural modernization. Despite the existence of a voluminous literature on outsourcing service of pest control, little is known about its effect on biopesticides use. To fill this knowledge gap, this study uses rice planting data from 1045 Chinese farm households to analyze the impact of different aging agricultural households and the pest control outsourcing service on the application of biopesticides by using the logit regression model. The study results showed that: (1) Participation in pest control outsourcing services significantly promotes biopesticide application. But this positive effect varied across age groups. (2) Compared with aging households, non-aging farmers tend to use biopesticides. Given this, it is recommended that pay attention to the ecological effect of pest control outsourcing services, strengthen the assistance to the aging labor group in the green pesticide promotion policy, and guide the aged planting decision makers to participate in pest control outsourcing services, thereby effectively improving the sustainable development of green agriculture.